A mini-core collection of 350 O. glaberrima accessions identified capturing more than 98% genetic variation - CGIAR Research Program on Rice (2021)
In a molecular diversity analysis of the AfricaRice O. glaberrima collection of >2000 accessions, 350 accessions were identified that captured >98% of the genetic variation in the collection.